Autologous versus pooled human serum for articular chondrocyte growth - Sha'ban, Munirah; Idrus, Ruszymah; Osman Cassim, Samsudin; M. Yusuf, Badrul Akmal Hisham; Baharudin, Azmi; Saim, Aminuddin (BioMed Central Ltd., 2008)
Purpose. To evaluate the effect of autologous human serum (AHS) versus pooled human serum (PHS) versus foetal bovine serum (FBS) for growth of articular chondrocytes and formation of chondrocytefibrin constructs. Methods. Experiments with monolayer culture expansion of human articular chondrocytes were performed using basic culture media supplemented with 10% AHS, PHS, or FBS. Growth kinetics and specific phenotypic expression of the serially expanded chondrocytes were evaluated. Largescale culture expansion was used to obtain about 30 million cells to form chondrocyte-fibrin constructs. All constructs were implanted subcutaneously at the dorsum part of athymic nude mice for 8 weeks. The in vivo constructs were evaluated using histological and gene expression studies. Results. The morphology of primary cultured chondrocytes (P0) was polygonal and became more elongated and larger after serial passages (P1, P2, and P3). This was comparable for AHS, PHS, and FBS. Total cell yields accumulated for AHS (28 million) and PHS (41 million) were significantly higher than those for FBS (4 million). After 8 weeks of implantation, in vivo chondrocyte-fibrin constructs demonstrated a glistening white and firm texture, comparable to normal hyaline cartilage. All constructs exhibited histo-architectural characteristics of well-distributed cartilage-isolated cells embedded within basophilic ground substance. Presence of accumulated proteoglycans cartilage-rich matrix was indicated by positive orange-red Safranin O staining. During monolayer culture expansion, collagen type II gene expression was down-regulated, while collagen type I gene expression was up-regulated. Collagen type II—the specific chondrogenesis marker—was reexpressed in the in vivo chondrocyte-fibrin construct. Conclusion. AHS and PHS are better than FBS for in vitro cultivation of human articular chondrocytes.